Potential of herbaceous legume cover crop fallow systems in the savanna zone - Carsky, R.J. (2000)
A set of herbaceous legumes was screened in the northern Guinea savanna zone of Nigeria in 1993-1994 to assess the ecological adaptability of the species and to observe characteristics that would influence their suitability in farming or cropping systems. Their fertilizer replacement value was estimated and the effects of P application to legumes in rotation with maize were examined. The following species were selected: cowpea, Mucuna pruriens var. cochinchinensis, Lablab purpureus, and Crotalaria ochroleuca. It was found that the legume rotation effect is small because the dry season is long and much of the residue disappears due to fire, wind, termites, or grazing. The N-fertilizer requirement can be reduced by applying P to legumes, but N fertilizer will still be needed for maize grain yields of 2.5 t/ha or more. KEYWORDS: TROPAG